2015
DOI: 10.1080/09540121.2015.1058895
|View full text |Cite
|
Sign up to set email alerts
|

Health-care providers’ experiences with opt-out HIV testing: a systematic review

Abstract: HIV is now a manageable chronic disease with a good prognosis, but early detection and referral for treatment are vital. In opt-out HIV testing, patients are informed that they will be tested unless they decline. This qualitative systematic review explored the experiences, attitudes, barriers, and facilitators of opt-out HIV testing from a health-care provider (HCP) perspective. Four articles were included in the synthesis and reported on findings from approximately 70 participants, representing diverse geogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
(60 reference statements)
0
19
0
Order By: Relevance
“…We reviewed and synthesised qualitative research documenting PWUD and provider experiences of integrated OST and HIV care. Qualitative research, and reviews of it, is valuable for understanding how care is experienced which can inform appropriate and acceptable services (Glenton, Lewin, & Gülmezoglu, 2016; Jones et al, 2014; Leidel, Wilson, McConigley, Boldy, & Girdler, 2015; Treloar & Rhodes, 2009; Tuthill, McGrath, & Young, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We reviewed and synthesised qualitative research documenting PWUD and provider experiences of integrated OST and HIV care. Qualitative research, and reviews of it, is valuable for understanding how care is experienced which can inform appropriate and acceptable services (Glenton, Lewin, & Gülmezoglu, 2016; Jones et al, 2014; Leidel, Wilson, McConigley, Boldy, & Girdler, 2015; Treloar & Rhodes, 2009; Tuthill, McGrath, & Young, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings do not support their rationale. On the contrary, perhaps the barrier is not the scope of practice per se as much as it is a lack of knowledge and training, time, space, confidentiality, and burdensome consent processes that might prevent dental professionals from offering the screening as discussed by Hutchinson et al 12 and Leidel et al 14 Furthermore, our study found that a formal relationship with health care professional support was a facilitator of this type of service.…”
Section: Discussionmentioning
confidence: 60%
“…The importance of training in HIV, counseling skills, and testing procedures to successfully carry out POC HIV screening cannot be overstated 3 , 13 , 14 . Greenberg et al argued that most barriers to successful implementation of POC HIV screening could be addressed with additional education and practical implementation strategies 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the epidemic, it has become clear the attendance, care, caution and concern of professionals during their care for the PLHIV, demystifying the proximity of death and considering AIDS as a chronic condition which requires comprehensive and constant care. In this sense, international studies also reveal that HIV is being considered as chronic, evolving from a life-threatening infection to a manageable condition in the long term due to advances in medicine, radical changes in health and social assistance policies, and the impact of population aging, with early detection and referral to treatment being vital (16)(17) .…”
Section: Discussionmentioning
confidence: 99%